Kompetensi SDM dan Manajemen Ramping (Lean) terhadap Kinerja Operasional pada Rumah Sakit Swasta di Kota dan Kabupaten Serang dengan Budaya Organisasi sebagai Variabel Intervening - Lestari, Novi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
With the increasing population in Indonesia, it has resulted in an increase in patients coming to the hospital, including in Banten Province, especially in the City and District of Serang. Even though hospitals in Banten Province are increasing every year, the accumulation of patients in hospitals still occurs. Efficient hospital services are one of the determinants of hospital quality so that they are able to use all available resources to generate profits as desired. This requires hospitals to improve operational performance by increasing the competence of human resources and Manajemen Ramping (Lean management) which has been quite widely applied in hospitals today. The results showed that 4 hypotheses were accepted while 3 hypotheses were rejected. HR competence has a significant effect on hospital operational performance. Manajemen Ramping (Lean management) has a positive and significant effect on the operational performance of the hospital. Meanwhile, organizational culture has no significant effect on improving hospital operational performance. HR competence has a positive and significant effect on organizational culture. Lean management also has a positive and significant effect on organizational culture. Then the indirect relationship between HR competence on hospital operational performance through organizational culture has a positive but not significant effect, as well as the indirect relationship between Manajemen Ramping (Lean management) on operational performance through organizational culture has a positive but not significant effect. So the conclusion of this study is that both exogenous variables are good predictors for predicting hospital operational performance.